LATE RECURRENCE OF CHOROIDAL NEOVASCULARIZATION IN PATIENTS WITH MULTIFOCAL CHOROIDITIS: CLINICAL SURVEILLANCE IN PERPETUITY. Issue Volume 16:Issues 2(2022) (13th November 2019) - Orellana-Rios, Jorge; Leong, Belinda C. S.; Fernández-Avellaneda, Pedro; Gattoussi, Sarra; Freund, K. Bailey; Yannuzzi, Lawrence A.
Abstract : We report a highly unusual series of elderly patients with idiopathic multifocal choroiditis and secondary choroidal neovascularization after several decades. They were successfully treated with intravitreal injections of anti–vascular endothelial growth factor medication. Hence, the importance of clinical surveillance of such patients over the course of many years is highlighted. Abstract : Purpose: To report a very late recurrence of choroidal neovascularization (CNV) in elderly patients with noninfectious multifocal choroiditis (MFC). Methods: Retrospective case series of patients with MFC with confirmed recurrence of CNV. Choroidal neovascularization was diagnosed with multimodal imaging, including optical coherence tomography angiography. Multifocal choroiditis–associated CNV eyes were treated with intravitreal injections of anti–vascular endothelial growth factor medication. Results: Four eyes of three patients were included in our study, with a mean (range) age of 73 years (67–78). The period between the original CNV and the recurrence was 53 years, with a range of 48–60 years. The mean number (range) of injections given after the late recurrence per eye was 7 (5–11). The mean duration (range) of follow-up post-treatment initiation was 93 (40–122) weeks. All eyes improved to 20/30 visual acuity or better at 6 months after initial treatment. Conclusion: Patients with MFC are never exempt from recurrent CNV, warranting follow-up in perpetuity. Age-related factors are important to consider which may increase the susceptibility for activating MFC-associated CNV in elderly people. Macular neovascularization could respond to a standard approach to management, in these patients with MFC, by a judicious use of intravitreal injections of anti–vascular endothelial growth factor therapy.